2014
DOI: 10.1039/c4cp01023j
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport in films of Geobacter sulfurreducens on graphite electrodes as a function of film thickness

Abstract: Harnessing, and understanding the mechanisms of growth and activity of, biofilms of electroactive bacteria (EAB) on solid electrodes is of increasing interest, for application to microbial fuel and electrolysis cells. Microbial electrochemical cell technology can be used to generate electricity, or higher value chemicals, from organic waste. The capability of biofilms of electroactive bacteria to transfer electrons to solid anodes is a key feature of this emerging technology, yet the electron transfer mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 55 publications
(104 reference statements)
1
27
2
Order By: Relevance
“…The capacity of some microorganisms to exchange electrons with electrical conductive materials as part of their metabolism is one of the most fascinating mechanisms in the field of microbiology . This phenomenon typically occurs in an electroactive biofilm in which all bacterial layers contribute to converting oxidative metabolism into electrical current …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The capacity of some microorganisms to exchange electrons with electrical conductive materials as part of their metabolism is one of the most fascinating mechanisms in the field of microbiology . This phenomenon typically occurs in an electroactive biofilm in which all bacterial layers contribute to converting oxidative metabolism into electrical current …”
Section: Introductionmentioning
confidence: 99%
“…In principle, this seems reasonable owing to the requirement of the existence of redox chemistry between the cells and an insoluble material, which would be satisfied by a biofilm architecture. Unfortunately, the main drawback of this scenario is the limited reactivity of the cells, which depends on the active area of the electrode in which the bioelectrochemical reaction is occurring (commonly reduced to the first 50 μm layer of the biofilm) . Interestingly, in electroactive biofilms, the cells located in the outer layers are at lower redox potentials and electron transfer is proposed to occur between bacteria under a different protein‐based scenario .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work examining the charge transfer properties of G. sulfurreducens biofilms, grown under controlled applied potentials, has shown that biocatalytic current, generated from oxidation of acetate, scales with applied potential 3 . The acetate oxidation currents do not scale directly to biofilm thickness 4 , however, suggesting that either mass or charge transport limits the overall current or that the biofilm formed over time displays differences in bacterial cell densities, viability and/or redox response. Besides this uncertainty, the mechanism by which electrons are transferred over long distances (>50 µm) through G. sulfurreducens biofilm to the solid electrode still remains unclear.…”
Section: Introductionmentioning
confidence: 99%